Development and validation of an endoscopic activity score for canine inflammatory bowel disease. Issue 3 (March 2015) - Slovak, J.E.; Wang, C.; Sun, Y.; Otoni, C.; Morrison, J.; Deitz, K.; LeVine, D.; Jergens, A.E.
Highlights The endoscopic activity score correlates with the endoscopist's assessment of abnormal mucosal appearance. Mucosal assessment is consistent when evaluated in patients different than that used for score development. The activity score incorporates mucosal variables intuitively considered as important by experienced endoscopists. The activity score incorporates mucosal variables previously shown to be reproducibly collected, and is itself reproducible. The activity score is simple to calculate.